Enhancing Community Musculoskeletal Health through an Integrated Physiotherapy Approach in Klitren Village - Hana Kristina; Nathan Agwin Khenda; Yekhonya Arkananta Pramahesta; Therese Karunia Rosari; Hemas Mulyarinta Wibowo; Aura Diva Ariyanti; Viona; Maria Verga Clarista Silab; Gabriel Wildan; Benediktus Gerrard Satya Dewa; Daniel Valentino Rendra K (Jurnal Abdimas, 2026)
Musculoskeletal disorders and reduced physical function are common health problems that may affect individuals across different age groups and contribute to decreased independence and quality of life. This community-based program aimed to promote musculoskeletal health through integrated health screening, exercise training, and physiotherapy services in Klitren Village, Yogyakarta City, Indonesia. The program was conducted in April 2026 and involved 98 participants aged 12–78 years. The activities included health screening, musculoskeletal assessment, postural screening using the REEDCO method, exercise and stretching training, and physiotherapy intervention. Health screening identified elevated blood glucose levels in 25 participants (25.5%), elevated uric acid levels in 13 participants (13.3%), and elevated cholesterol levels in 8 participants (8.2%). Musculoskeletal assessment revealed shoulder pain (27 participants), back pain (22 participants), and knee pain (14 participants) as the most frequently reported complaints. Postural assessment was performed in 34 participants, identifying severe postural deviations in six individuals. Twenty-one participants received physiotherapy interventions consisting of manual therapy and therapeutic exercise. Program evaluation demonstrated a 98% satisfaction rate, while more than 90% of participants reported good understanding of the exercise program and willingness to continue exercising independently at home. This integrated community-based approach may facilitate early identification of health and musculoskeletal problems, improve exercise awareness, and support self-management strategies. Future programs should incorporate regular follow-up and long-term evaluation to assess the sustainability of exercise adherence and health outcomes.